2022
DOI: 10.1021/acsanm.2c02697
|View full text |Cite
|
Sign up to set email alerts
|

Tribochemistry of Graphene Oxide/Graphene Confined between Iron Oxide Substrates: Implications for Graphene-Based Lubricants

Abstract: Graphene has been widely tested as a lubricant material for steel sliding contact in engineering applications. The structural and chemical evolutions on friction surfaces are critical to understand the improvement of tribology performance in experiments. Here, we used the reactive molecular dynamics (ReaxFF-MD) simulations to study the friction and wear behaviors of a monolayer graphene oxide or graphene (GO/Gr) flake confined between two amorphous iron oxide substrates. The results show that when under lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“… 67 Hence, our study elucidates key concepts of relevance for different contact junctions—lubricated either by liquid dispersions of graphene or by other wet-transferred 2D flakes 2 , 68 , 69 —that are operated under nominally wearless sliding conditions or do involve more complex tribochemistry and third-body-effects. 8 , 70 …”
Section: Resultsmentioning
confidence: 99%
“… 67 Hence, our study elucidates key concepts of relevance for different contact junctions—lubricated either by liquid dispersions of graphene or by other wet-transferred 2D flakes 2 , 68 , 69 —that are operated under nominally wearless sliding conditions or do involve more complex tribochemistry and third-body-effects. 8 , 70 …”
Section: Resultsmentioning
confidence: 99%
“…One theoretical study showed that the barrier energy and shear strength for graphene/metal oxide interface is much lower than that of the chemisorbed interface between graphene and metal (without oxide formation) [49]. Another possible contributing factor is the folding and unfolding of rGO flakes within the 2D nanocomposites during friction, as predicted by a recent simulation study [50]. It may also be related to the elimination of atomic interlock and the block of chemical interactions between neighboring layers.…”
Section: Tribological Properties Of 2d Fe 2 O 3 /Rgo Nanocompositesmentioning
confidence: 99%
“…ReaxFF MD simulations can describe the breaking and formation of interatomic bonds and thus can be used to explain the occurrence of tribochemical reactions in materials. According to ReaxFF MD simulations, Yu et al revealed the significance of shear stress in a tribo-oxidation reaction. Wang et al . found that the formation of interfacial C–Fe bonds has a remarkable influence on the tribological performances of steel sliding contacts.…”
Section: Introductionmentioning
confidence: 99%